Retention and Clinical Performance of Zirconia Crowns: A Comprehensive Review - Fatemeh Soleimani; Hamid Jalali; Azam Sadat Mostafavi; Somayeh Zeighami; Maryam Memarian (International Journal of Dentistry)
Zirconia has been used for rehabilitation of edentulous spaces approximately for a decade, and there have been several reports regarding the clinical performance and retention of zirconia crowns. Outstanding mechanical properties, biocompatibility, and excellent aesthetics make zirconia-based crowns as a popular crown among the current all-ceramic crowns in restorative dentistry. However, restoration with a zirconia crown is a challenging treatment. The goal of this study was to assess the current literature to summarize the studies reporting the effective risk factors on retention of zirconia crowns to provide clinicians with a useful point of view in the decision-making process for use of these restorations. Literature based-search was performed to find related articles until August 2020 using EMBASE, Google Scholar, and MEDLINE. Search terms used were “zirconia restorations properties,” “zirconia crowns clinical performance,” “zirconia crown survival,” “biological complications,” and “zirconia crown retention.” Results were limited to papers available in English. The references of all related literature were also searched for further citations. Overall, although clinical long-term and follow-up studies are a vital requirement to conclude that zirconia has great reliability, it seems that zirconia crown restorations are both well tolerated and sufficiently resistant.